Natural, human and spatial constraints to expanding populations of otters in the Iberian Peninsula - Clavero, Miguel; Hermoso, Virgilio; Brotons, Lluís; Delibes, Miguel (Journal of Biogeography, 2010)
Aim To determine the relationships between otter (Lutra lutra) distribution dynamics and environmental and spatial constraints over a 20-year period. Location Andalusia, southern Iberian Peninsula. Methods We synthesized otter distribution data from three otter surveys (1985, 1995 and 2005) using subcatchment areas defined by hydrological barriers. Subcatchments were characterized by two ‘natural’ (climatic and orographic variables) and two ‘human’ (land use and population density) gradients. In addition, we calculated two contagion variables (the distance to previously occupied subcatchments and the percentage of occupied subcatchments within a 50 km buffer) for consecutively surveyed subcatchments. Results Between 1985 and 2005 the percentage of subcatchments with otters present increased from 42% to 72%. Otters tended to be rare or absent from human-dominated areas. Anthropogenic gradients were better predictors of otter distribution than natural ones. Human and natural gradients showed strong covariation, but for any value of the natural gradients otters tended to be present in subcatchments with lower human impacts. Colonization of new subcatchments was found to be strongly related to contagion variables and expansion rates were slower than those estimated in other studies. Newly colonized areas tended to be located in areas with intermediate human influence, while repeated absences occurred mainly in areas where human impact was most severe. Main conclusions Our results suggest that recent otter expansion across Andalusia is a reflection of large-scale improvement in environmental conditions. Otter populations that survived the period of strong and generalized declines appear to be acting as sources from which neighbouring areas are colonized, probably aided by improved water quality and increases in food availability. However, the further expansion of otters into their full original range is likely to be constrained by human-impacted landscapes.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Andalusia; freshwater environments; landscape gradients; Lutra lutra; mammals; Mediterranean streams; otter surveys; recolonization; recovering species

Mammals and fire in mediterranean ecosystems Ecological responses from the shrew Crocidura russula (Insectivora Soricidae) and the rodent Eliomys quercinus (Gliridae) in burned cork oak forest - Fons, R.; Grabulosa, I.; Marchand, B.; Miquel, J.; Feliu, C.; Mas-Coma, S. (VIE ET MILIEU-LIFE AND ENVIRONMENT, 1996)
Mammals and fire in mediterranean ecosystems. Ecological responses from the shrew Crocidura russula (Insectivora - Soricidae) and the rodent Eliomys quercinus (Gliridae) in burned crock oak forest. In the present work we report the ecological responses of two small mammals to fire. During a six-year post-fire period, both species were studied by the capture-mark-recapture on a 9 ha quadrate established in a recently burned cork oak forest. The white-toothed-shrew, Crocidura russula, was the least resistant species to fire, disappearing completely during the first two years. Reappearing on the third year, the population maintained a low effective with the same fluctuation similar to that observed within the control. Although faster than on other studied mediterranean ecosystems, its allochthonous ristablishment on the burned cork oak forest, seems to be dependent on the litter reconstitution. Due to its rupicolous habits, its biotope specialization, highly favored by the presence of rocks on the capture quadrate, and some physiological apects (hibernation), the dormouse Eliomys quercinus, showed a better pre-adaptive response to the post-fire stress. The survival of a nucleus of autochtonous individuals insured, from the first year, a slow, but progressive recovery of the population.
The following values have no corresponding Zotero field: pub-location: LABORATOIRE ARAGO, BP 44, 66651 BANYULS-SUR-MER CEDEX, FRANCE publisher: OBSERVATOIRE OCEANOLOGIQUE BANYULS
Keywords: Cork Oak Forest; Crocidura russula; ELIOMYS QUERCINUS; fire; mammals